Investigation of temporal changes in immune responses to Mycobacterium bovis in cattle and African buffaloes (Syncerus caffer). - Clarke, Charlene (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.